Effects of Nitrate Stress on Physiological and Biochemical Characteristics of Canna generalis Bailey at Seedling Stage - Zhaohu GU; Shuxin ZHAO; Wenwei WU; Huini XU; Kunzhi LI (Guangdong nongye kexue)
【Objective】The physiological and biochemical mechanisms of Canna generalis Bailey seedlings in response to nitrate stress were studied in order to provide a basis for improving water eutrophication by planting Canna generalis Bailey.【Method】Using Yunnan Canna generalis bailey as the material, hydroponic methods were used to study the nitrogen uptake, seedling growth, photosynthetic parameters, antioxidant enzyme activity as well as physiological and biochemical indexes of Canna generalis bailey under different nitrate nitrogen treatments.【Result】After treatment with 0 (CK), 10, 50, 100 and 150 mmol/L nitrate solutions for 5 weeks, the total nitrate uptake amounts of Canna generalis Bailey was 0, 411.7, 676.9, 554.6 and 516.4 mg/plant, the plant height increased by -0.27, 5.25, 4.25, 0.05 and -10.32 cm, and the fresh weight increased by 10.3, 32.7, 31.6, 20.3 and -11.0 g/plant, respectively. Within 5 weeks of hydroponic treatment, the photosynthesis and transpiration rates of 10 mmol/L and 50 mmol/L low concentration nitrate were significantly higher than those of the control. In the fifth week, the photosynthesis rate was about 11 and 15 times that of CK, and the transpiration rate was 4.3 and 7.5 times that of CK. Stomatal conductance and intercellular CO2 concentration remained high. The photosynthesis and transpiration rates of plants treated with 100 and 150 mmol/L nitrate solutions were at a low level, and the stomatal conductance was extremely low. The activities of SOD and CAT under 0 and 10 mmol/L treatments were relatively low, while those under 50, 100 and 150 mmol/L treatments were significantly higher than those in the control. The activities of SOD and CAT under 50 mmol/L treatment were the highest and significantly higher than those under other treatments. POD activity was significantly higher at 50 mmol/L than that of other treatments within 5 weeks, and the lowest at 150 mmol/L, indicating that high concentration of NO3- inhibited POD enzyme activity.【Conclusion】A lower concentration of 50 mmol/L nitrate can enhance the photosynthesis, antioxidant enzyme activity, and nitrate nitrogen absorption of Canna generalis Bailey, promoting its growth. However, a higher concentration of 100 mmol/L nitrate reduces the photosynthesis, antioxidant enzyme activity, and nitrate nitrogen absorption of Canna generalis Bailey, inhibiting its growth.